Effects of Different Voided Urine Sample Storage Time, Temperature, and Preservatives on Analysis with Multiplex Bead-Based Oncuria Bladder Cancer Immunoassay - Sunao Tanaka; Kaoru Murakami; Toru Sakatani; Riko Lee; Wayne Hogrefe; Fernando Siguencia; Charles J. Rosser; Hideki Furuya (Diagnostics)
Background/Objectives: Urinalysis accuracy requires reliable sample stability that is dependent on the chosen collection and storage conditions. The multiplex Oncuria bladder cancer immunoassay currently needs urine samples stored at 4 °C until analysis, which requires more effort, equipment, and workflow than storing samples at room temperature. Thus, successful sample storage at room temperature (20 °C) may reduce laboratory handling time and expenses. This study evaluated whether different voided urine sample collection and storage parameters affected subsequent biomarker analysis with Oncuria. The Oncuria simultaneously quantifies 10 protein analytes in urine to generate a bladder cancer diagnostic signature. Methods: Samples were stored at varied temperatures (20 °C, 4 °C, −20 °C) for up to 1 month. The effects of adding two commercial urine sample stabilizers and antibiotics (trimethoprim) were also assessed. Subsequently, multiple potential biospecimen stabilizers were tested in urine samples and evaluated with Oncuria in hopes of allowing the urine sample to remain at room temperature for extended periods of time. Results: First, it was demonstrated that voided urine samples stored at room temperate without such stabilizers had different levels of the 10 analytes associated with the Oncuria test compared to voided urine samples stored at 4 °C. Next, we evaluated the effects of commercially available biospecimen stabilizers. Despite the addition of these stabilizers, the levels of the 10 analytes were altered when the samples were stored at room temperature for prolonged periods of time. Therefore, we could not identify a suitable biospecimen stabilizer that would not require sample refrigeration. Conclusions: To minimize sample degradation/alteration after collection, voided urine samples should be refrigerated until analyzed with Oncuria as the refrigeration is advantageous for the storage and the transport of these urine samples.